Pelatihan Penerapan Disiplin Positif pada Sekolah Jenjang Sekolah Dasar (SD) di Kabupaten Soppeng - Andi Puspa Sari Idris; Patang; Jamaluddin; Subariyanto; Marhayati (Jurnal Ragam Pengabdian, 2025)
This training aims to implement positive discipline in elementary schools in Soppeng Regency. The training method applied is participatory training; namely, all participants actively participate in conveying their experiences of implementing positive discipline in their schools during the training. The results of the training were that all participants made a commitment to implement positive discipline in schools according to their respective roles, namely as teachers, principals, and school supervisors. In addition, participants were able to formulate the implementation of positive discipline through examples of real problems in their respective schools and will apply the results of the training in their respective schools.